2000
DOI: 10.1021/ja001491q
|View full text |Cite
|
Sign up to set email alerts
|

Hydrido, Halo, and Hydrido-Halo Complexes of Two-Electron Mixed-Valence Diiridium Cores

Abstract: Two-electron mixed-valence bimetallic cores of iridium are stabilized in a diphosphazane, MeN[P(OCH2CF3)2]2 (bis(bis(trifluoroethoxy)phosphino)methylamine, tfepma) coordination sphere. Treatment of [Ir(cod)Cl]2 with tfepma affords the Ir2 0,II complex, Ir2(tfepma)3Cl2 (1), in which the Ir0 and IrII centers assume trigonal bipyramidal and square pyramidal coordination geometries, respectively. The coordinatively unsaturated two-electron mixed-valence core of 1 supports an extensive acid−base and oxidation−reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
71
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 79 publications
2
71
0
Order By: Relevance
“…[44] Nocera has reported that the mixed-valence, unsaturated, 32-electron, Ir 2 dimer 18 reversibly adds H 2 across the IrIr bond to form saturated dihydride 19. [45] Purging with N 2 recovers 18. The mechanism is suggested to proceed by addition of H 2 to one metal centre and then hydride migration rather than the symmetry-forbidden concerted 1,2 addition.…”
Section: Equilibrium Reversible (H 2 Is Lost Upon Removal Of the H 2 mentioning
confidence: 95%
“…[44] Nocera has reported that the mixed-valence, unsaturated, 32-electron, Ir 2 dimer 18 reversibly adds H 2 across the IrIr bond to form saturated dihydride 19. [45] Purging with N 2 recovers 18. The mechanism is suggested to proceed by addition of H 2 to one metal centre and then hydride migration rather than the symmetry-forbidden concerted 1,2 addition.…”
Section: Equilibrium Reversible (H 2 Is Lost Upon Removal Of the H 2 mentioning
confidence: 95%
“…The A–D–A ligands, bis(difluorophosphino)methylamine (dfpma, CH 3 N(PF 2 ) 2 ) and bis(bistrifluoroethoxyphosphino)methylamine (tfepma, CH 3 N[P(OCH 2 CF 3 ) 2 ] 2 ) shown in Chart 1, exhibit a particular proclivity for promoting the internal disproportionation of binuclear M 2 I,I cores to M 2 0,II cores 65 for the metals of rhodium 57,58 and iridium. 59–61,66 X-ray crystal structures reveal a pronounced asymmetry in the diphosphazane framework upon ligation to a bimetallic core derived from the asymmetric stabilization of metals that differ by two in their formal oxidation. The result is consistent with π-donation of the amine bridgehead lone pair to the PR F 2 bonded to M II .…”
Section: A Chemist’s Toolbox For Catalysis Of Consequence To Renewmentioning
confidence: 99%
“…Our success in using M n ⋯M n+2 species to drive two- and four-electron transformations along ground and excited state pathways 5759 established two-electron mixed valency as a useful design concept for the development of multielectron reaction schemes. The two-electron mixed valence core is particularly effective in hydrogen management and production.…”
Section: A Chemist’s Toolbox For Catalysis Of Consequence To Renewmentioning
confidence: 99%
“…Redox-active ligands have initially been utilized primarily to induce two-electron transformations at metal centers that are redox-inert, prone to undergo one-electron processes,o r that are lacking delectrons to induce two-electron bond activation processes. [6] Alternatively,e lectron repulsion between two electron-rich elements can destabilize ar educed state, thereby inducing reactivity. [4] Synthetic systems featuring metal-metal interactions have successfully been exploited to facilitate (multi-electron) chemical transformations.…”
mentioning
confidence: 99%